Garden of lamentations - Crombie, Deborah (New York, NY William Morrow, an imprint of HarperCollinsPublishers, 2017)
"While Gemma James investigates the murder of a young nanny who may be one of a series of victims, Duncan Kincaid uncovers information that puts those closest to him in danger"--Publisher.
The pretty girl in the white dress looks as if she's sleeping. But Reagan Keating has been murdered, and the lead detective, DI Kerry Boatman, turns to Gemma James for help. Gemma has a personal connection to the case: Reagan was the nanny of a child who attends the same dance studio as Toby, Gemma and Kincaid's son. Meanwhile Kincaid finds himself plagued by disturbing questions about several previous-- and seemingly unrelated-- cases involving members of the force. If his suspicions are correct and the crimes are linked, are his family and friends in mortal danger as well?
Map on endpapers.
106182
Keywords: Kincaid, Duncan -- (Fictitious character) -- Fiction; James, Gemma -- (Fictitious character from Crombie); Police -- England -- London -- Fiction; Women detectives -- Fiction; Murder -- Investigation -- Fiction; London (England) -- Fiction; England -- London; Detective and mystery fiction; Fiction; Mystery fiction